Sanitizing the national body: COVID-19 and the revival of Japan's "Closed Country" strategy. (September 2022) - Vogt, Gabriele; Qin, Sian
Japan's handling of border control measures during the COVID-19 pandemic has become known as sakoku -approach. Sakoku literally means "closed country" and generally refers to a historic period when the Tokugawa Shogunate (1603–1868) kept Japan's borders shut because international contacts were feared to cause public upheaval and political instability. While these times have long passed, contemporary Japan, too, is known for its tight management of immigration avenues. In the light of the COVID-19 pandemic, most of these avenues were cut off, and despite much criticism, have remained largely inaccessible for two years now. In this paper, we build on concepts from authoritarian populism and the performance of crisis to analyze how and why Japan revived its isolationist strategy. We decipher the discursive framings that Prime Minister Abe applied to illustrate the disruptive influence that open borders would have on Japan's public health, social stability and by extension, on the national body itself. We argue that from the onset of the pandemic on, the ethnic others were portrayed as a risk mainly for two intertwined reasons: Firstly, Japan's pandemic management relies on self-constraint rather than rules and sanctions, and the ethnic others' compliance was not fully trusted. Secondly, this exclusionary strategy fed into populist discourses and was presumed to result in favorable support rates for the administration.